Reading Disability and Quality of Life Based on Both Self- and Parent-Reports: Importance of Gender Differences - Balazs, Judit; Miklosi, Monika; Toro, Krisztina T.; Nagy-Varga, Diana (Frontiers in Psychology, 2016)
Purpose: The aim of this study is to investigate self- and parent-rated quality of life (QoL) in children with a reading disability (RD) and the impact of comorbid psychopathology, with special focus on age and gender differences. Methods: Using the Dyslexia Differential Diagnosis Maastricht-Hungarian standard test, 127 children (aged < 18) were included in the RD group and 81 in the control group. To measure comorbid psychopathology, the Strengths and Difficulties Questionnaire (SDQ) was administered. To evaluate the children’s QoL self- and parent-rated versions of the Measure of Quality of Life for Children and Adolescents (ILK) were used. Group differences in QoL and psychopathology were assessed using Mann-Whitney U tests. Moderated mediational models were tested in which comorbid psychopathology mediated the relationship between group membership and self- and parent-rated QoL, which was dependent on gender. Child’s age and parents’ level of education were included as covariates. Results: The RD group showed lower QoL than the controls in several domains, according to the parent-report, while no differences between the two groups were found, according to self-report. In boys, results revealed conditional and indirect effects of group membership on self- and parent-rated QoL through comorbid psychopathology (-.046, BCa 95%CI: -.135 −.043 and .064, BCa 95%CI: .024−.111, respectively) as well as a conditional direct effect of group membership on parent-reported (-.098, BCa 95%CI: .012−.184), but not self-rated, QoL. No relationship was found for girls. Conclusions: This study highlights the importance of measuring QoL and comorbid psychopathology in children with RDs from more sources and accounting for gender and age differences.